Federalism and Third Tier Governance in Nigeria: Panacea for Grassroots Democracy and Development - Fnim, Steve Eboka (Kashere Journal of Politics and International Relations, 2025)
Local Governments or grassroots Government have since the 1976 reforms acquired an increased role and relevance particularly due to the efforts of the military Government propelled reforms. Most importantly, the reforms assigned to local governments, the status of a “third tier” government in the federal state arrangement. The reference to local government as a third tier level of government with clear cut functions and responsibilities is now common both in legal and political usages. However, the meaning of a third-tier status has remained assumed and contestable. The question of resolving the dilemma of the actual status of local government has gained currency and impetus. The need to further consolidates on these changes and entrench a virile and truly independent third-tier system of local government constitute focus of this work. The research will be structured into four sections. The first section shall deal with the general introduction of the study, objectives, problems and procedure followed by analysis of the conceptual framework. The third segment will consider the impact of infrastructural development undertaken by some local governments in Delta State. Finally, necessary recommendations for the way forward will be preferred.